2016
DOI: 10.1111/jfd.12447
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils to control ichthyophthiriasis in pacu, Piaractus mesopotamicus (Holmberg): special emphasis on treatment with Melaleuca alternifolia

Abstract: In vitro effect of the Melaleuca alternifolia, Lavandula angustifolia and Mentha piperita essential oils (EOs) against Ichthyophthirius multifiliis and in vivo effect of M. alternifolia for treating ichthyophthiriasis in one of the most important South American fish, Piaractus mesopotamicus (Holmberg), were evaluated. The in vitro test consisted of three EOs, each at concentrations of 57 μL L(-1) , 114 μL L (-1) , 227 μL L(-1) and 455 μL L (-1) , which were assessed once an hour for 4 h in microtitre plates (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Regarding the herbal medicines studied here, the tea tree, Melaleuca alternifolia (Maiden & Betche) Cheel, is known for its powerful antiseptic effect (Thomsen et al., ). Recently, the essential oil (EO) of the tea tree has been described to have promising antiparasitic and bactericidal action against fish pathogens when used in water (Steverding, Morgan, Tkaczynski, Walder & Tinsley, ; Valladão et al., ). However, to the best of our knowledge, the use of tea tree EO in the diet and its effect on the general status of healthy fish and intestinal mucosa is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the herbal medicines studied here, the tea tree, Melaleuca alternifolia (Maiden & Betche) Cheel, is known for its powerful antiseptic effect (Thomsen et al., ). Recently, the essential oil (EO) of the tea tree has been described to have promising antiparasitic and bactericidal action against fish pathogens when used in water (Steverding, Morgan, Tkaczynski, Walder & Tinsley, ; Valladão et al., ). However, to the best of our knowledge, the use of tea tree EO in the diet and its effect on the general status of healthy fish and intestinal mucosa is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Peppermint, Mentha piperita L., is known to have beneficial effects on gastrointestinal tissue, immunomodulating actions and chemopreventive potential (McKay & Blumberg, ). Recently, some authors have shown that peppermint EO has antiparasitic effect against Ichthyophthirius multifiliis (Valladão et al., ) and monogeneans (Costa et al., ; Hashimoto et al., ; Malheiros, Maciel, Videira & Tavares‐Dias, ), and when used in water did not cause negative effects on fish haematology (Hashimoto et al., ). The enhancement of haematological and immune parameters was observed in rainbow trout, Oncorhynchus mykiss (Walbaum) (Adel, Pourgholam, Zorriehzahra & Ghiasi, ), and Caspian white fish, Rutilus frisii kutum (Kamenskii) (Adel, Amiri, Zorriehzahra, Nematolahi & Esteban, ), fed with ethanolic extract of peppermint, and in Asian seabass, Lates calcarifer (Bloch), fed with a powder of peppermint leaves (Talpur, ).…”
Section: Introductionmentioning
confidence: 99%
“…In O. niloticus, eugenol at 286.5 mg L À1 caused 100% mortality (Vidal et al, 2008). A study on Piaractus mesopotamicus reported that almost 50% of the fish did not survive exposure to Melaleuca alternifolia (Valladão et al, 2016). In addition, mortality among Brycon hilarii exposed to eugenol at 250 mg L À1 (Fabiani et al, 2013), hybrid P. mesopotamicus x Piaractus brachypomus exposed to 50 mg L À1 (Rodrigues et al, 2015), Centropomus undecimalis exposed to 75 mg L À1 (Bernardes-J unior et al, 2013) and Cyprinus carpio exposed to 0.08 mg L À1 (Kamble et al, 2014) has been reported.…”
Section: Toxicity Of Essential Oils and Their Major Compounds In Fishmentioning
confidence: 99%
“…Cytotoxic properties are of great importance in applications of EOs, not only against certain pathogens that have been widely reported (Bakkali et al, 2008;Maryam et al, 2015;Sharifi-Rad et al, 2017), but also in relation to different parasites (Novato et al, 2015, Valladão et al, 2016. EOs have a very close interaction with the phospholipids of cell membranes due to the short extent of their carbon chains and high hydrophobicity of their constituents (Maryam et al, 2015).…”
Section: In Vitro Activity Of Essential Oils On Fish Parasitesmentioning
confidence: 99%
See 1 more Smart Citation